Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s12944-019-1042-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of familial hypercholesterolemia-associated genes on the phenotype of premature myocardial infarction

Abstract: Background The incidence of premature myocardial infarction (PMI) has gradually increased in recent years. Genetics plays a central role in the development of PMI. Familial hypercholesterolemia (FH) is one of the most common genetic disorders of cholesterol metabolism leading to PMI. Objective This study investigated the relationship between FH-associated genes and the phenotype of PMI to clarify the genetic spectrum of PMI diseases. Method T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…In case 3, the patient had a PCSK9 missense c.277C>T mutation on p.Arg93Cys (rs151193009). There are conflicting findings whether this particular mutation is pathogenic, a variant of uncertain significance, or benign [ 28 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case 3, the patient had a PCSK9 missense c.277C>T mutation on p.Arg93Cys (rs151193009). There are conflicting findings whether this particular mutation is pathogenic, a variant of uncertain significance, or benign [ 28 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of this patient showed a missense c.277C>T mutation in the PCSK9 gene (rs151193009), which was located within exon 2. There are conflicting findings whether this particular mutation is pathogenic, a variant of uncertain significance, or benign [28][29][30][31].…”
Section: Casementioning
confidence: 99%
“…Genetics play a critical role in the progression of PMI, with a heritability of 63% [ 6 ]. Additional evidence reveals that proprotein convertase subtilisin/kexin type 9 (Pcsk9) relates to cholesterol homeostasis, is a risk factor for PMI [ 7 9 ]. As a relatively new PMI risk factor, Pcsk9 has received widespread attention for elevating plasma low-density lipoprotein cholesterol levels due to promote degradation of LDL receptor in the liver [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…PA is also a protective factor for the incidence of MI (18), although another study indicated that PA is not significantly associated with the risk of acute MI (19). Family history of premature coronary artery disease plays an important role in the development of MI (10). Many studies showed that identifying individuals with an increased risk of MI is a major challenge for enhancing prevention.…”
Section: Introductionmentioning
confidence: 99%